КОВУЛ АСАЛШИРАЛИ ВА ШИФОБАХШ ЎСИМЛИК (Multidisciplinary Journal of Science and Technology, 2025)
In this article, the cultivation technology, biology, importance in agriculture and agriculture, chemical composition and medicinal composition of the Capparist plant are covered.